Experiencing film music : a listener's companion - LaFave, Kenneth (Lanham : Rowman & Littlefield, 2017)
LaFave opens the ears of film-goers to the nuance behind movie music, laying out in layman's language how composers map what we hear to what we see. As part of the Listener's Companion series, this volume provides an enhanced experience of music by exploring how the works were written and first performed as well as how they are enjoyed today.
Timeline -- Introduction -- The not-so-silent era -- Max Steiner and the first generation -- Spotlight : spotting and the click track -- Mysteries, thrillers, and film noir -- Spotlight : orchestrators -- The epic, the exotic, and war -- Cowboys and superheroes -- Drama -- Spotlight : jazz in film music -- Theme songs, comedies, and romantic comedies -- Spotlight : animation -- Science fiction and fantasy -- Ambient music, no music, and ready-mades -- Trends, forecasts, and innovations.
Includes bibliographical references and index.
Keywords: Motion picture music -- Analysis, appreciation